DETERMINANTS OF PROFITABILITY OF MICRO-AGRICULTURAL ENTERPRISES FROM THE REPUBLIC OF SERBIA - Tekić, Dragana; Mutavdžić, Beba; Milić, Dragan; Zekić, Vladislav; Novaković, Tihomir; Popov, Milana (Ekonomija - teorija i praksa, 2023)
The paper analyzes the determinants of profitability of microagricultural enterprises that operated in the Republic of Serbia, the analysis was carried out for the period from 2010 to 2019. Using panel regression analysis, the influence of various microeconomic and macroeconomic determinants on profitability, measured by the rate of return on assets, was examined. The following indicators were observed as microeconomic determinants of profitability: liquidity, financial leverage, indebtedness, asset structure indicator, total business asset turnover ratio, fixed asset turnover ratio, current asset turnover ratio, inventory turnover ratio, trade receivables turnover ratio and sales rate. Indicators of the growth rate of the gross domestic product and inflation were observed as macroeconomic determinants of profitability. Based on the results of the panel regression analysis, it was determined that the turnover ratio of total business assets, the turnover ratio of current assets and the growth rate of the gross domestic product have a positive and statistically significant influence on the profitability of the observed companies. Indebtedness, an indicator of asset structure and the turnover ratio of fixed assets have a negative and statistically significant impact on the profitability of the observed companies. It is expected that the obtained results will be useful to all interested parties in agribusiness, primarily in the context of the analysis of factors that have been determined to have a negative impact on the profitability of the observed companies.